Tuberculous severe acute colitis. A case report. (September 2021) - Haddad, A.; Sebai, A.; Chelly, B.; Maghrebi, H.; Chaker, Y.; Jouini, M.; Kacem, M.
Abstract: Introduction: and importance: Intestinal tuberculosis represents 2% of the ten million cases of tuberculosis reported in 2018. Herein, we report a case of tuberculous severe acute colitis. It is a rare and life-threatening condition. Our literature review found only five published cases. It occurs generally in immunocompromised patients. Extended colonic inflammation seems to be the main predictive factor of death. Moreover, an early diagnosis and rapid onset of antituberculous treatment are mandatory to save the patient's life. Case presentation: Herein, we present a case of tuberculous severe acute colitis with a review of the reported cases. The patient presented with a severe and idiopathic acute colitis. He was put on broad-spectrum antibiotics and intravenous corticosteroids. At day two, he developed septic shock and colic perforation. Colectomy was performed. Microbiology investigation and pathology examination confirmed tuberculous colitis. Clinical discussion: Tuberculous severe acute colitis occurs generally in immunocompromised patients. Extended colic inflammation seems to be the main predictive factor of death. Moreover, an early diagnosis and rapid onset of antituberculous treatment are mandatory to save the patient's life. However, diagnosis is difficult as symptoms aren't specific. Microbiology and pathology were compulsory to retain colic tuberculosis in all the reported cases. Conclusion: Tuberculous severe acute colitis is a challenging and life-threatening condition. It usually occurs in immunocompromised patients. Abdominal CT-scan may evoke the diagnosis. Microbiology and pathology are mandatory to retain the diagnosis. Early diagnosis and onset of antituberculous treatment are compulsory to save the patient's life. Highlights: Diagnosis of tuberculous severe acute colitis is difficult. It usually occurs in immunocompromised patients. Surgery is mandatory if perforation occurs. Early diagnosis and onset of antituberculous treatment are compulsory to save the patient's life.